2020
DOI: 10.35137/jabk.v7i1.374
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PENGENDALIAN INTERNAL DAN BUKTI AUDIT TERHADAP OPINI AUDIT (Studi Empiris di Kantor Akuntan Publik di Jakarta Timur)

Abstract: The population in this study amounted to 40 KAP in the East Jakarta area. The sample in this study uses Cluster Sampling, with the criteria for respondents submitted to the Director of Public Accountants by IAI. Data obtained by collecting questionnaires directly to respondents as many as 42 and 42 returned questionnaires, as well as 38 questionnaires that can be processed. Internal Control and Audit Evidence have a significant and positive effect on Audit Opinion and simultaneous results indicate that the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Weaknesses of SPI include not recording / not being done or inaccurate, the report preparation process is not following the provisions, the entity is late in submitting reports, inadequate accounting and reporting information systems, and accounting and reporting information systems not supported by adequate human resources. (Winarto, 2020) in the research that has been conducted, obtained partial hypothesis testing results (t-test) of internal control, it can be concluded that partially internal control has a significant effect on audit opinion. This shows that auditors who have good internal control will easily provide their audit opinion.…”
Section: Effectiveness and Efficiency (Effectiveness And Efficiency)mentioning
confidence: 95%
“…Weaknesses of SPI include not recording / not being done or inaccurate, the report preparation process is not following the provisions, the entity is late in submitting reports, inadequate accounting and reporting information systems, and accounting and reporting information systems not supported by adequate human resources. (Winarto, 2020) in the research that has been conducted, obtained partial hypothesis testing results (t-test) of internal control, it can be concluded that partially internal control has a significant effect on audit opinion. This shows that auditors who have good internal control will easily provide their audit opinion.…”
Section: Effectiveness and Efficiency (Effectiveness And Efficiency)mentioning
confidence: 95%
“…Menurut PP Nomor 60 tahun 2008 menyatakan bahwa sistem pengendalian intern adalah proses yang integral pada tindakan dan kegiatan yang dilakukan secara terusmenerus oleh pimpinan dan seluruh pegawai untuk memberikan keyakinan memadai atas tercapainya tujuan organisasi melalui kegiatan yang efektif dan efisien, keandalan pelaporan keuangan, pengamanan aset Negara, dan ketaatan terhadap peraturan perundang-undangan. .36778/jesya.v6i2.1154 Pengendalian internal adalah proses, kebijakan, dan prosedur yang dirancang oleh manajemen untuk memastikan pelaporan keuangan yang andal dan pembuatan laporan keuangan sesuai dengan kerangka akuntansi yang berlaku untuk memastikan pelaporan Internal gendara keuangan membahas hal-hal seperti sikap manajemen terhadap gendara, kompetensi pegawai inti/kunci , penilaian risiko, akuntansi, dan sistem informasi keuangan lainnya yang digunakan, serta kegiatan gendara keuangan (Winarto, 2020). Berdasarkan landasan teoritis penalaran internal, kita dapat melihat bahwa penalaran internal adalah prosedur yang dirancang untuk dilakukan oleh orang-orang untuk memberi mereka informasi penting yang diperlukan untuk pencapaian tujuan tertentu yang terkait erat dengan tujuan mereka sendiri.…”
Section: Pendahuluanunclassified